Resilience: A primer - Hoddinott, John F. (International Food Policy Research Institute, 2014)
Recurrent humanitarian crises have led many development actors to begin thinking differently about development issues. Rather than placing humanitarian assistance, governance, food security and nutrition, economic development, and other topics in separate silos, many are using the concept of resilience to join up their myriad activities.